Taxonomic notes on Cretarophalis patrickmuelleri Wichard, 2017 (Insecta: Neuroptera: Nevrorthidae) from the mid-Cretaceous of Myanmar, and its phylogenetic significance - Lu, Xiumei; Xia, Fangyuan; Wang, Bo; Aspöck, Ulrike; Liu, Xingyue (Zootaxa, 2018)
Nevrorthidae is a family of Neuroptera with low species diversity, disjunct geographic distributions, and a controversial phylogenetic status. Previous fossil records of the family are from the Eocene except for the recently described species Cretarophalis patrickmuelleri Wichard, 2017 from mid-Cretaceous Burmese amber, following earlier records of an undescribed species. However, such a significant finding of this family from Mesozoic was originally presented only with a preliminary description. Here we re-describe the species based on exquisitely preserved materials from mid-Cretaceous Burmese amber that provides for a much more detailed description, in particular of the hindwing, female genitalia, and larval head. Furthermore, distinctive morphological characters of C. patrickmuelleri with significant phylogenetic relevance are discussed. The general morphology, particularly that of the larva, has changed little between the Mesozoic and Cenozoic, and it reflects an evolutionary stasis that might correspond to their aquatic larval life-style. The present finding also supports the relictual nature of the modern nevrorthids.